Spectrum of lithium induced thyroid abnormalities: a current perspective - Kibirige Davis (Thyroid Research, 2013)
Abstract Background Lithium is an integral drug used in the management of acute mania, unipolar and bipolar depression and prophylaxis of bipolar disorders. Thyroid abnormalities associated with treatment with lithium have been widely reported in medical literature to date. These include goitre, hypothyroidism, hyperthyroidism and autoimmune thyroiditis. This current review explores the varied thyroid abnormalities frequently encountered among patients on lithium therapy and their management, since lithium is still a fundamental and widely drug used in psychiatry and Internal Medicine. Methods PubMed database and Google scholar were used to search for relevant English language articles relating to lithium therapy and thyroid abnormalities up to December 2012. The search terms used were lithium treatment, thyroid abnormalities, thyroid dysfunction, goitre, hypothyroidism, hyperthyroidism, thyrotoxicosis, autoimmune thyroiditis, lithium toxicity, treatment of affective disorders and depression and side effects of antipsychotic drugs. Reference lists of the identified articles were further used to identify other studies. Results Lithium affects normal thyroid functioning through multiple mechanisms. At the cellular level, it decreases thyroid hormone synthesis and release. It also decreases peripheral deiodination of tetraiodothyronine (T4) or thyroxine by decreasing the activity of type I 5’ de-iodinase enzyme. Hypothyroidism and goitre (clinically and/ultrasonographically detected) are the most prevalent thyroid abnormalities among patients on long term lithium therapy. Lithium induced hyperthyroidism is very infrequent. Lithium increases the propensity to thyroid autoimmunity in susceptible individuals due to its effect of augmenting the activity of B lymphocytes and reducing the ratio of circulating suppressor to cytotoxic T cells. Conclusions Thyroid function tests (serum thyroid stimulating hormone, free thyroid hormones-T4 and triiodothyronine [T3] concentrations and thyroid auto-antibodies) and assessment of thyroid size clinically and by thyroid ultrasonography ought to be performed among patients initiating lithium therapy at baseline and later annually. More frequent assessment of thyroid function status and size during the course of therapy is recommended among middle aged females (≥50 years), patients with a family history of thyroid disease and those positive for thyroid auto-antibodies (anti-thyroid peroxidase and TSH receptor antibodies).